Islamic Perspectives Relating to Business, Arts, Culture and Communication 2015
DOI: 10.1007/978-981-287-429-0_35
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Satisfaction with the University Cafeteria: Structural Relationships of Food Quality, Staff, Price Fairness, and Ambiance

Abstract: This study aims to investigate the relationship between the food quality, price fairness, staff, and ambiance of the university cafeteria with students' satisfaction. To test the conceptual model and test the proposed hypotheses, a quantitative survey was performed via a structured self-administered questionnaire among 78 undergraduates from Universiti Teknologi MARA (UiTM), Sabah campus, Malaysia, utilizing convenience sampling method. Data was analyzed using structural equation modeling (SEM) technique via A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Hyun et al (2018) concluded that the ambiance and aesthetics of a facility stimulate positive attitudes and promote perceived value, customer satisfaction and loyalty. Ambiance is considered as important as food and service quality in influencing the customers’ attitudes and behaviors following their dining experience (Chang et al , 2015; Ha and Jang, 2010). Ambiance often refers to the design of the foodservice setting, which proposes that stimulating the customers’ state of mind and can influence their purchasing decision along with their future intentions to revisit the foodservice outlets, and recommend to others (Ali et al , 2016; Ryu and Jang, 2008).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Hyun et al (2018) concluded that the ambiance and aesthetics of a facility stimulate positive attitudes and promote perceived value, customer satisfaction and loyalty. Ambiance is considered as important as food and service quality in influencing the customers’ attitudes and behaviors following their dining experience (Chang et al , 2015; Ha and Jang, 2010). Ambiance often refers to the design of the foodservice setting, which proposes that stimulating the customers’ state of mind and can influence their purchasing decision along with their future intentions to revisit the foodservice outlets, and recommend to others (Ali et al , 2016; Ryu and Jang, 2008).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Jani and Han (2014) as well as Wakefield and Blodgett (1996) found that nonvisual elements of atmospherics, including background music, scent and temperature, may have a subconscious effect on customers. Chang et al (2015) as well as Ha and Jang (2010) found that atmospherics are just as critical as service quality and food quality in shaping the customers' opinion of their dining experience as well as their behavioral intention. Barnes et al (2016a, b), Canny (2014), as well as Swimberghe and Wooldridge (2014) found a substantial connection between atmospherics and overall customer satisfaction.…”
Section: Convenience Convenience According Tomentioning
confidence: 99%